Performance and muscle architecture comparisons between starters and nonstarters in National Collegiate Athletic Association Division I women's soccer - Jajtner, A. R.; Hoffman, J. R.; Scanlon, T. C.; Wells, A. J.; Townsend, J. R.; Beyer, K. S.; Mangine, G. T.; McCormack, W. P.; Bohner, J. D.; Fragala, M. S.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2013)
This study compared performance and muscle architecture (MA) changes in starters (S) and nonstarters (NS) during a National Collegiate Athletic Association Division I women's soccer season. Twenty-eight women (19.9 ± 1.1 years; 1.71 ± 0.08 m; 64.7 ± 6.4 kg) were monitored for vertical jump power (VJP), repeated line drills (LDs), 3-dimensional multiple object tracking (3D-MOT), and reaction time (RT) at preseason, midseason, and postseason. Muscle architecture changes using ultrasonography were assessed at preseason and postseason. Comparisons between S (n = 11; 70.0 ± 14.6 min per game) and NS (n = 17; 8.4 ± 8.0 min per game) were performed to make magnitude-based inferences. No differences were seen in VJP during the season in either group. Starters were more likely (81.1%) to decrease LD time than NS, with no differences in fatigue rate. Starters and NS improved 3D-MOT (1.14 ± 0.41 to 1.55 ± 0.43) and RT (0.37 ± 0.05 to 0.34 ± 0.33 seconds), with no differences between groups. Rectus femoris (RF) echo intensity improved (65.57 ± 1.50 to 61.26 ± 1.59) in both groups, with no interactions observed. Cross-sectional area (20.84 ± 3.58 to 21.46 ± 3.66 cm2) increased and pennation angle (PANG) (12.58 ± 2.56 to 11.78 ± 2.03°) decreased for both groups in the vastus lateralis (VL). Muscle architecture comparisons between groups revealed S likely decreased VL muscle thickness (MT) and PANG (81.6 and 79.4%, respectively) and possibly decreased RF MT and PANG (65.7 and 59.4%, respectively) when compared with NS. Results indicate that VJP and LD fatigue rate are not changed during a competitive season, but S become faster than NS. Three-dimensional multiple object tracking and RT improve regardless of playing time. Changes in MA indicate that practices alone provide sufficient stimulus for improving muscle quality during the competitive season.